Surgical treatment of mandibular osteoma – case report (Research, Society and Development, 2020)
Osteomas are benign neoplasms that are characterized by the proliferation of mature compact or spongy bone. The most frequent sites of occurrence are the mandible and paranasal sinuses. The purpose of this article is to report the diagnosis and surgical treatment of a mandibular peripheral osteoma in a non-syndromic patient. Male patient, 40 years old, ASA I, sought the service of Maxillofacial Surgery at Hospital Universitário Oswaldo Cruz - PE with a complaint of increased intraoral volume in the anterior region of the mandible, firm palpation, well delimited and about 2 cm. After physical examination, the diagnostic hypothesis raised was osteoma and mandibular torus. The planned surgical proposal was intra-oral access, excision of the lesion, mandibular osteoplasty and referral of the material collected for histopathological analysis to confirm the diagnosis. Histopathological analysis confirmed the diagnostic hypothesis of peripheral osteoma. The patient was followed up in the postoperative period and after 6 months of the surgical procedure, no signs of recurrence were observed.